Th1 and Th17 Cells and Associated Cytokines Discriminate among Clinically Isolated Syndrome and Multiple Sclerosis Phenotypes - Arellano, Gabriel; Acuña, Eric; Reyes, Lilian I.; Ottum, Payton A.; De Sarno, Patrizia; Villarroel, Luis; Ciampi, Ethel; Uribe-San Martín, Reinaldo; Cárcamo, Claudia; Naves, Rodrigo (Frontiers in Immunology, 2017)
Multiple Sclerosis (MS) is a chronic, inflammatory and demyelinating disease of the central nervous system. It is a heterogeneous pathology that can follow different clinical courses, which may be led by distinct effector mechanisms. Limited and controversial information has been reported in relation to the progression of the immune response across MS phenotypes. Here, we aimed to determine differences in cytokine levels, cell frequencies and their ratios among different MS clinical subtypes. Blood samples from untreated patients diagnosed with clinically isolated syndrome (CIS) (n=21), different clinical forms of MS (n=62) [relapsing remitting (RRMS), secondary progressive (SPMS) and primary progressive (PPMS)], and healthy controls (HC) (n=17), were tested for plasma levels of IFN-γ, IL-10, TGF-β, IL-17A, and IL-17F by immunoanalysis. Th1 and Th17 lymphocyte frequencies were determined by flow cytometry. Our results showed that IFN- levels and the IFN-γ/IL-10 ratio were significantly higher in CIS patients than in RRMS and HC. Th1 cell frequencies were significantly higher in CIS and RRMS than in progressive MS. The Th1/Th17 cell ratio was significantly skewed toward Th1 in CIS compared to RRMS, SPMS, PPMS and HC. The Th17 cell frequency was significantly higher in RRMS compared to CIS. Receiver operating characteristic (ROC) statistical analysis determined that IFN-γ, the IFN-γ/IL-10 ratio, Th1 cell frequency and the Th1/Th17 cell ratio discriminated among CIS and MS subtypes. A subanalysis among patients expressing high IL-17F levels showed that RRMS and PPMS patients had a polarization toward Th17 compared to CIS and HC, and IL-17F and the IFN-γ/IL-17F ratio discriminated between disease subtypes. Overall, our data shows that CIS and MS phenotypes display distinct Th1 and Th17-related cytokine and cell profiles. These immune parameters discriminated between clinical forms and suggested a shift from Th1 into Th17 across MS subtypes. Upon validation, they might be useful as biomarkers to predict disease progression.